PROFESSIONAL ORIENTATION OF THE COURSE «COMPUTER INFORMATION TECHNOLOGY» AT STUDYING OF SPREADSHEETS - Valko Н.В. (Journal of Information Technologies in Education (ITE), 2010)
In work the examples of statement of the theme «Studying of spreadsheets» in course «Computer information technology» which promote effective mastering of a material, and also the further application of the received knowledge under production conditions are resulted